Factors affecting the adoption of e-payment systems by university students: extending the TAM with trust. (2018) - Salloum, Said A.; Al-Emran, Mostafa
Studying the adoption of e-payment systems is not a new research topic. However, studying the factors affecting the adoption of e-payment systems in the higher educational institutions is a topic of great importance. Therefore, this study is considered the first that attempts to examine the factors affecting the e-payment systems adoption in nine different universities in the United Arab of Emirates (UAE). A total number of 528 students participated in the study. The technology acceptance model (TAM) was extended with the trust factor to examine the students' intention to use the e-payment systems. The partial least squares-structural equation modelling (PLS-SEM) approach was used to validate the developed model. The empirical results suggested that trust is a significant factor in predicting the perceived usefulness, perceived ease of use, and e-payment adoption. The perceived ease of use is also found to be a significant determinant that affects the perceived usefulness and e-payment adoption. Surprisingly, perceived usefulness is found to be insignificant in determining the e-payment adoption.